Comparison between core needle biopsy and excisional biopsy for breast neoplasm. Issue 34 (27th August 2021) - Sun, Chunjie; Lu, Qun; Zhang, Xinrong; Zhang, Yuehong; Jia, Shuai; Wang, Jing; Zhu, Hailun; He, Wen; Zhang, Zhongqiu
Abstract : Abstract: This study aimed to explore clinical significance of core needle biopsy (CNB) in pathological diagnosis of breast neoplasm. Seventy one breast neoplasm samples were obtained from Tongzhou Maternal and Child Health Hospital of Beijing between the years of 2006 and 2014. Forty five specimens were obtained via CNB and cases offering 26 of them received neoadjuvant chemotherapy. Pathology, histology, and immunohistochemistry results were compared between CNB specimens and excisional biopsy. Upward and downward tendencies could be observed in CNB specimens and excisional biopsy, respectively, in all items. Tumor proportion of CNB tissues was (33 + 2)/45 = 77.78%, when ductal carcinoma in situ detected by both CNB and excisional biopsy was 31/45 = 68.89%, with a consistency of (31 + 3)/45 = 75.56%. Tumor thrombus detected by both CNB and excisional biopsy was 2/45 = 4.44%. Among cases receiving neoadjuvant chemotherapy, CNB and excisional biopsy, in mitotic figure, cytological scoring and histological grading, showed a total change rate of >50% (50%–75%), while changes in duct and cellular heteromorphism were not distinct. Cases showing changes were up to 73.08%, with 8/26 = 30.77% for rise and 11/26 = 42.31% for descent. CNB could be used for preoperative diagnosis of breast neoplasm, and help to determine proper treatment regimen, thus elevating the rate of breast conserving. However, this method still has several limitations, particularly in immunohistochemical tests of human epidermal receptor protein-2. Neoadjuvant chemotherapy may influence the accuracy of CNB diagnosis.